Beyond Scale and Scope: Exploring Economic Drivers of U.S. Specialty Crop Production With an Application to Edamame - Neill, Clinton L.; Morgan, Kimberly L. (Frontiers in Sustainable Food Systems, 2021)
Specialty crops are considered high-risk, high-reward, yet growers face differing and relatively larger risk exposure when compared to traditional row crops. With traditional row crops, economies of scale and scope are key factors to increasing economic profitability. However, increasing economic profit for specialty crop operations present challenges which limit grower ability to easily take advantage of scale and scope economies. The authors discuss production, finance, regulatory, price, and human resource risks unique to U.S.-grown specialty crops. We apply our economic risk assessment framework to analyze U.S. edamame and present strategies to manage and mitigate risks faced by growers. We conclude that edamame may represent a profitable alternative crop in the U.S., and suggest future research topics are needed to optimize yields and meet market demand.